Association of weight-adjusted-waist index with type 2 diabetes mellitus in Chinese urban adults: a cross-sectional study - Wu, Qingzheng; Li, Bing; Wang, Yuepeng; Zhang, Yue; Wang, Qian; Li, Binqi; Jing, Wei; Yang, Jing; Mu, Yiming (Frontiers in Endocrinology, 2025)
BackgroundRecently, weight-adjusted-waist index (WWI), a new index for evaluating obesity, has been developed. This study aimed to examine the association between WWI and T2DM in Chinese urban adults.MethodA total of 5,0978 eligible participants drawn from the prospective REACTION study (Cancer Risk Assessment in Chinese People with Diabetes) were included in this study. Participants were divided into 3 groups based on baseline WWI levels. Pearson correlation analysis and binary logistic regression analysis were conducted to explore the association of WWI with T2DM risk factors and with T2DM risk.ResultsThe prevalence of obesity, central obesity and T2DM was 14.2%, 46.8% and 11.0% respectively, with a median age of 57 years. Logistic analysis showed that the WWI was significantly associated with the risk of T2DM. Compared to the lowest tertile of WWI (T1) serving as the reference group, the second tertile (T2) and the third tertile (T3) were associated with a 0.218-fold [1.218 (1.152, 1.288), P <0.001] and 0.286-fold [1.286 (1.212, 1.364), P <0.001] increase in the odds of developing T2DM respectively. After adjusting for all factors with the exception of the stratified variable, this association held true in age, sex, BMI, hypertension, and hyperlipidemia subgroup and was especially pronounced in those aged <60 years, BMI ≥24 kg/m2, and males, with interactions between WWI and age, sex, and BMI (P for interaction <0.05).ConclusionWWI was positively associated with T2DM in Chinese urban adults, especially in young and middle-aged males with BMI ≥24 kg/m2.